2020
DOI: 10.1002/ehf2.12769
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs2070600 in advanced glycosylation end‐product specific receptor with prognosis of heart failure

Abstract: Aims Our objective was to investigate the association of common variants in the coding region of advanced glycosylation end-product specific receptor (RAGE) and the prognosis of heart failure (HF). Methods and results A total of 3394 HF patients were continuously enrolled from January 2009 to August 2018 with a median follow-up of 20.4 months. Additionally, 2861 healthy subjects also participated in the study. By sequencing these two groups, we identified a common functional missense variant rs2070600 in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…After searching from articles for reported polymorphisms, 24 available variants (Supporting Information, Table ) were then selected when compared with the WES data 13,21–40 . It is known from Supporting Information, Table that activation of the renin‐angiotensin‐aldosterone system (RAAS) and the adrenergic system is closely related to HF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After searching from articles for reported polymorphisms, 24 available variants (Supporting Information, Table ) were then selected when compared with the WES data 13,21–40 . It is known from Supporting Information, Table that activation of the renin‐angiotensin‐aldosterone system (RAAS) and the adrenergic system is closely related to HF.…”
Section: Resultsmentioning
confidence: 99%
“…After searching from articles for reported polymorphisms, 24 available variants (Supporting Information, Table S4 ) were then selected when compared with the WES data. 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 It is known from Supporting Information, Table S3 that activation of the renin‐angiotensin‐aldosterone system (RAAS) and the adrenergic system is closely related to HF. It is now well acknowledged that common variants in genes that encode neurohormonal, adrenergic, and intracellular proteins can modulate clinical consequences of HF patients.…”
Section: Resultsmentioning
confidence: 99%
“…PRTN3 [226], CX3CR1 [227], S100A12 [228], CSF2 [229], FGG (fibrinogen gamma chain) [230], LHX9 [231], MPO (myeloperoxidase) [232], F11 [233], S100A8 [234], CXCL11 [235], BPI (bactericidal permeability increasing protein) [236], BDNF (brain derived neurotrophic factor) [237], CXCL10 [238], S100A9 [239], IL1B [240], CXCR1 [241], CXCR2 [242], CYP1B1 [243], EDNRB (endothelin receptor type B) [244], CEBPA (CCAAT enhancer binding protein alpha) [245], CDH13 [246], GPX3 [247], FGF2 [248], SHH (sonic hedgehog signaling molecule) [249], VIP (vasoactive intestinal peptide) [250], KL (klotho) [251], SMAD6 [252], BMPR2 [253], APOA1 [254], TLR3 [255], GATA3 [256], CCR2 [257], CAV1 [258], TRPC3 [259], EPAS1 [260], SIGLEC14 [261], MAPK15 [262], DNAH5 [263] and AQP5 [264] were identified to be associated with chronic obstructive pulmonary disease. DEFA3 [265], CX3CR1 [266], S100A12 [161], TUBB1 [267], ANKRD1 [268], ADRA1A [269], FGG (fibrinogen gamma chain) [270], AGER (advanced glycosylation end-product specific receptor) [271], PF4 [272], FFAR2 [273], MPO (myeloperoxidase) [274], CD5L [275], HMGCS2 [164], RXFP1 [276], F11 [277], S100A8 [278], PGLYRP1 [279], VEGFD (vascular endothelial growth factor D) [280], CHRM2 [281], CBS (cystathionine beta-synthase) [282], BPI (bactericidal permeability increasing protein) [283], LRP2 [284], BDNF (brain derived neurotrophic factor) [285], GCOM1 [286], CXCL10 [287], ANGPTL7 [288], PRODH (proline dehydrogenase 1) [289], P2RY1 [290], LRRN4 [291], S100A9 […”
Section: Discussionmentioning
confidence: 99%
“…RAGE receptor binding was top GO pathways according to the molecular function.The receptor for AGEs (RAGE) has a critical role in SARS-CoV-2associated hyper in ammation and lung injury (24).And RAGE expression increased in HF samples compared with healthy donors (25).This suggested that we could intervene COVID- (27).Complement-induced blood clotting also played a critical role in COVID-19 and HF(28, 29).More and more evidences indicated that cytochrome P450 (CYP) played a role in the pathogenesis, progression and prognosis of HF. In ammation could inhibit the CYP enzyme, resulting in the increase of CYP would greatly accelerate the progression of HF in COVID-19 patients (30,31).Glutathione de ciency was the possible explanation for serious manifestation and death in COVID-19 patients (32).According some studies,modulation of glutamine metabolism might provide a new therapeutic strategy for HF and COVID-19 (33).It has been documented that atherosclerosis progression is closely associated with heart failure and can be used as a predictor of severity and susceptibility to SARS-COV-2 infection (34).At present, there is no evidence of common pathways between COVID-19 and African trypanosomiasis,Malaria, Chagas disease and Pertussis, and we need more tests to prove their relationship in the future.In this study, Pathway analysis helped us in upcoming treatments of HF and COVID-19 by intervening in the Pathway that we have analyzed.…”
Section: Discussionmentioning
confidence: 99%